2017
DOI: 10.1097/aln.0000000000001670
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Innovative Techniques for Monitoring Nociception during General Anesthesia

Abstract: Background This study compares the analgesic indices Analgesia Nociception Index (heart rate variability), Surgical Pleth Index (photoplethysmography), and pupillary dilatation, to heart rate, mean arterial pressure, and bispectral index, with regard to diagnostic accuracy and prediction probability for nociceptive response. The primary endpoint was the correlation between Δ values and the remifentanil dose administered. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 28 publications
2
63
0
2
Order By: Relevance
“…Similar results have been reported previously. 15 Despite its limitations, it may be the poor performance of the 'traditional' parameters such as MAP and HR which create an ongoing significant interest in SPI and similar tools to monitor nociception. Though closed-loop anaesthesia systems using either bispectral index alone or combining it with MAP or HR-based analgesia scores have been found feasible, 16e18 the analgesia component of such systems may require further research.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported previously. 15 Despite its limitations, it may be the poor performance of the 'traditional' parameters such as MAP and HR which create an ongoing significant interest in SPI and similar tools to monitor nociception. Though closed-loop anaesthesia systems using either bispectral index alone or combining it with MAP or HR-based analgesia scores have been found feasible, 16e18 the analgesia component of such systems may require further research.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we defined hemodynamic reactivity as an increase of more than 20% of either MBP or HR after 1 minute of painful stimulus. In adult patients, hemodynamic reactivity was often defined as an increase by more than 20% of HR and/or blood pressure within 5 min or following 2 min after noxious stimulation [6,21,25]. Through preliminary experiment, we found that in pediatric patients the hemodynamic response caused by nociception changes fast; Hemodynamic changes may have returned to normal five minutes after intubation or skin incision.…”
Section: Discussionmentioning
confidence: 93%
“…Researches have shown that these tools might reflect the nociception during general anesthesia [1,16,21]. However, these parameters are mainly aimed at adult patients and affected by arrhythmia alongside many heart rate affecting drugs [6,25]. Pain Rating Index (PRI) is a cerebral pain tolerance indicator based on EEG signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the surgical plethysmographic index (SPI) and analgesia nociception index (ANI), which use autonomic responses to measure noxious stimulation. [1][2][3][4] Response Entropy TM (RE) and…”
Section: Introductionmentioning
confidence: 99%